2012
DOI: 10.1007/s00586-012-2517-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative investigation of flexion relaxation phenomenon in healthy and chronic neck pain subjects

Abstract: Purpose The cervical flexion relaxation phenomenon (FRP) is a neck extensor myoelectric ''silence'' that occurs during complete cervical and lumbar flexion. In contrast to low back pain, the changes that occur during FRP in chronic neck pain (CNP) patients are still not clear. The aim of this study was to assess the characteristics of this phenomenon in the cervical region in CNP patients and controls. Methods Twenty-two women (23 ± 2.62 years) with chronic non-specific neck pain and 21 healthy women (23.4 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 39 publications
(78 reference statements)
3
42
1
7
Order By: Relevance
“…Wytrazek et al [41] also found a correlation between amount of EMG signal alteration and presence of active TP. It was also observed a reduced Flexor Relaxation Phenomena (FRP) in subjects with IOMNP, indicating an inability to relax the extensor muscles when maximal neck flexion occurs [42].…”
Section: Changes In Muscular Activation Patternmentioning
confidence: 89%
“…Wytrazek et al [41] also found a correlation between amount of EMG signal alteration and presence of active TP. It was also observed a reduced Flexor Relaxation Phenomena (FRP) in subjects with IOMNP, indicating an inability to relax the extensor muscles when maximal neck flexion occurs [42].…”
Section: Changes In Muscular Activation Patternmentioning
confidence: 89%
“…In the present study, ES myoelectric activity at full flexion increased 44% after sustained neck flexion and was followed by a significant decrease in the FRR. Previous studies on the cervical spine have suggested that FRR may be an important marker of neuromuscular impairment that differentiates neck pain from healthy control subjects (Maroufi et al, 2013;Murphy et al, 2010).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 97%
“…Then thorax was tightly fixed by a strap at the level of the scapula spine. The subjects then performed three trials in the following sequence and pace: maintain the starting position for 4 s (phase 1), complete cervical flexion in 4 s (phase 2), sustain cervical full flexion for 4 s (phase 3) and complete cervical re-extension from the fully flexed position to the starting position in 4 s (phase 4) (Maroufi et al, 2013).…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations